2000
DOI: 10.1053/jlts.2000.18472
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplantation tumor necrosis factor-α production predicts acute rejection after liver transplantation

Abstract: Immunosuppressive therapy has many adverse effects in both the short and longer term. Tailoring immunosuppression might be possible if pretransplantation parameters predicted rejection. We investigated production of the proinflammatory cytokine, tumor necrosis factor-␣ (TNF-␣), and the anti-inflammatory cytokine, interleukin-10 (IL-10), pretransplantation to determine whether there is a relation with acute rejection. Peripheral-blood mononuclear cells were obtained from patients with chronic liver disease on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
(32 reference statements)
2
9
1
Order By: Relevance
“…In accordance with results from this animal study, human studies investigating pre-and post-transplant in vitro cytokine responses did not find an association between differential production of IL-10 and the occurrence of acute liver graft rejection [14,151. Since LEW and PVG did not differ in rejection grade and in vitro TNF-a responses, our results neither support nor contradict previous studies showing an association between higher in vitro production of TNF-a and the occurrence of acute human liver graft rejection [14, 151. In conclusion, different inbred rat strains could be classified as high-, intermediate-or low-responders with regard to in vitro TNF-a, IFN-y, IL-6 and IL-10 production since naive animals of different strains show differences in their capacity to produce cytokines upon a standardized in vitro stimulus.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with results from this animal study, human studies investigating pre-and post-transplant in vitro cytokine responses did not find an association between differential production of IL-10 and the occurrence of acute liver graft rejection [14,151. Since LEW and PVG did not differ in rejection grade and in vitro TNF-a responses, our results neither support nor contradict previous studies showing an association between higher in vitro production of TNF-a and the occurrence of acute human liver graft rejection [14, 151. In conclusion, different inbred rat strains could be classified as high-, intermediate-or low-responders with regard to in vitro TNF-a, IFN-y, IL-6 and IL-10 production since naive animals of different strains show differences in their capacity to produce cytokines upon a standardized in vitro stimulus.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, some cytokine gene polymorphisms have been associated with the occurrence of human solid organ graft rejection [9, 10,11,12,131. More recently, differential levels of in vitro TNF-alpha production have also been associated with human liver allograft rejection [14,151. In vitro cytokiiie responses can be affected by factors such as age, underlying disease and immunosuppressive therapy [16,17,181.…”
mentioning
confidence: 99%
“…Thus, depending on the cytokines that are present when antigen activation occurs, innate immune cells including macrophages, dendric cells and NK cells, may acquire cytopathic and/or immunoregulatory phenotypes. TNF-α is primarily produced by monocytes or macrophages, it has been demonstrated that pre-transplant in vitro production of this molecule was significantly increased in patients with post-transplant acute rejection compared with those who did not develop acute rejection (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…They control the activation and differentiation of immune effector cells and mediate cytotoxic activity of the effector cells. It has been suggested that Type I CD4 + and CD8 + T cells (Th1, Tc1) cytokines (interleukin-2, interferon- and tumor necrosis factor (TNF)-) might promote cellular rejection [1][2][3] , whereas type II CD4 + and CD8 + T cells (Th2, Tc2) cytokines (interleukin-4 and interleukin-10) might suppress graft rejection [4] . T cells stimulated via the T-cell receptors (TCRs) not only proliferate, but also undergo subsequent apoptosis by activation-induced cell death (AICD) [5,6] .…”
Section: Introductionmentioning
confidence: 99%